EVALUATION OF FOURTEEN GRASS POPULATIONS AS FORAGE CROPS FOR SOUTHWESTERN SASKATCHEWAN - LAWRENCE, T.; RATZLAFF, D. C. (Canadian Journal of Plant Science, 1985)
Fourteen grass populations were evaluated for stand establishment, persistence, and dry matter yield under dryland conditions. Of these populations, Agropyron desertorum was most suitable for hay and Elymus angustus for pasture. Bromus biebersteinii compared favorably with Elymus junceus for pasture, suggesting that the two should be compared under grazing. When grown in mixture with alfalfa E. angustus and E. karataviensis tended to maintain a 50:50 grass-legume stand, whereas A. desertorum, A. cristatum × A. desertorum (4N), B. biebersteinii, B. inermis and E. junceus were very competitive and kept the percentage of alfalfa in the stand low. Both Elymus dahuricus and Elymus sibiricus showed good initial production and were short lived, suggesting they might be useful for enhancing the early production from other species sown in widely spaced rows. Elymus karataviensis was persistent but low yielding. Arctagrostis latifolia and Deschampsia beringensis were low yielding and lacked persistence.Key words: Hay, pasture, Arctagrostis, Agropyron, Bromus, Deschampsia, Elymus